2021
DOI: 10.33221/jiiki.v11i01.956
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Nursing Students’ Attitude Towards Research: A Survey in a Philippine Higher Education Institution

Abstract: Introduction: Research is one of the competencies expected of a beginning professional nurse. While research attitude has been widely explored among nursing students internationally, there is limited published research among nursing students in the Philippines. Objective: This study was conducted to find out the factors associated with attitude towards research among nursing students. Method: The design of this study cross-sectional with 79 undergraduate third-year nursing students in one higher ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
0
1
2
Order By: Relevance
“…Even so, they had a positive attitude toward research usefulness for the profession aspect, Interest in scientific research aspect, and relevance to life aspect. These results are like previous studies [16], [17], [22]. This means that nursing students were interested in scientific research and are aware of its usefulness, and its important role of scientific research in their future work.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Even so, they had a positive attitude toward research usefulness for the profession aspect, Interest in scientific research aspect, and relevance to life aspect. These results are like previous studies [16], [17], [22]. This means that nursing students were interested in scientific research and are aware of its usefulness, and its important role of scientific research in their future work.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that the attitude toward scientific research of nursing students did not have a high positive level. The mean score of the overall scale for all participants in this study was slightly lower than that of previous studies [17], [22]. Using the same tool, Oducado (2021) and Iloh (2020) found that the mean score of the overall scale was 4.91 ± 0.67 and 5.02 ± 0.96.…”
Section: Discussioncontrasting
confidence: 68%
“…Sự khác biệt này có thể do học phần NCKH chưa cung cấp đủ kiến thức, kỹ năng nghiên cứu cho sinh viên khiến họ cảm thấy khó khăn, lo lắng và thiếu tự tin trong nghiên cứu. Thật vậy, nghiên cứu đã chứng minh kiến thức và năng lực nghiên cứu chưa tốt có thể ảnh hưởng tiêu cực lên thái độ của sinh viên với nghiên cứu [10]. Do đó, cần đơn giản hóa phương pháp giảng dạy học phần NCKH, không quá tập trung vào lý thuyết, thay vào đó là tăng cường kỹ năng thực hành nghiên cứu.…”
Section: Bàn Luậnunclassified
“…Nghiên cứu hiện tại không tìm ra mối liên quan giữa giới tính, dân tộc và điểm học tập tích lũy của SVĐD và thái độ đối với NCKH. Kết quả này tương đồng với nghiên cứu trước của Furaikh (2017), Halabi (2016) và Oducado (2021) [2], [8], [10]. Tuy nhiên, cần có các nghiên cứu tiếp theo để kiểm chứng lại mối liên quan này.…”
Section: Bàn Luậnunclassified